2020
DOI: 10.1080/10717544.2020.1775724
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional magnetite nanoparticles to enable delivery of siRNA for the potential treatment of Alzheimer’s

Abstract: Therapeutic drugs for Alzheimer’s disease have been extensively studied due to its recurrence and abundance among neurodegenerative diseases. It is thought that the accumulation of amyloid precursor protein (APP) products, a consequence of an up-regulation of the β-site APP-cleaving enzyme 1 (BACE1), is the main triggering mechanism during the early stages of the disease. This study aims to explore the ability of a multifunctional conjugate based on magnetite nanoparticles for the cellular delivery of siRNA ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
(45 reference statements)
4
31
0
Order By: Relevance
“…Figure 7 B exemplifies how large nanobioconjugate clusters can be also internalized and accumulate without altering cell morphology. We believe that the pendant groups of PEA facilitate cell penetration, as has been previously described by us and others [ 33 , 79 ]. In particular, the intermingling with glycosaminoglycans and phospholipids in the membrane appear to be involved in bypassing the bilayer [ 80 ].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Figure 7 B exemplifies how large nanobioconjugate clusters can be also internalized and accumulate without altering cell morphology. We believe that the pendant groups of PEA facilitate cell penetration, as has been previously described by us and others [ 33 , 79 ]. In particular, the intermingling with glycosaminoglycans and phospholipids in the membrane appear to be involved in bypassing the bilayer [ 80 ].…”
Section: Resultssupporting
confidence: 69%
“…Moreover, it has been reported that native RNase 3 tends to accumulate in the specialized primary lysosomes of eosinophil cells, which provides further evidence of the tendency of our MNPs-RNase 3/1 nanobioconjugates to remain trapped in the lysosomal compartments of macrophages [78]. In contrast, other studies conducted by our research group demonstrated that functionalized MNPs without immobilized protein have lower colocalization with lysosomal compartments in comparison to MNPs-RNases [79]. Figure 7B exemplifies how large nanobioconjugate clusters can be also internalized and accumulate without altering cell morphology.…”
Section: Translocation Of Nanobioconjugates and Intracellular Colocalsupporting
confidence: 64%
“…The nanomaterials capable of withholding different chemistries on their surfaces, such as antibodies, small interfering RNA (siRNA), or peptides, are of great interest, particularly in the medical field [ 39 , 40 ]. In our case, we are interested in the conjugation of translocating peptides and proteins for efficient cell penetration and endosomal escape.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we also designed multifunctional orthopyridyl disulfide-PEG succimidyl ester (OPSS-PEG-NHS) coated IONs to enable the delivery of siRNA for silencing the BACE1 gene expression, as potential treatment of Alzheimer’s disease. The immobilization of OmpA on the surface of these PEGylated IONs increased their endosomal escape efficiency in neuroblastoma cells from 68% to 88%, demonstrating the potent escape abilities of this protein [ 269 ].…”
Section: Enhancing Ion Endosomal Escapementioning
confidence: 99%
“…Hybrid ION/UCNP systems have been widely applied in cancer therapy, MRI and diagnosis, gene therapy, and drug delivery [ 308 ]. In general, the most prevalent host matrices for iron oxide core-shell nanoparticles include Y 2 O 3 , Y 2 O 2 S, LaF 3 , BaYF 5 , NaYF 4 , and NaGdF 4 , which have been doped with Yb 3+ /Tm 3+ and Yb 3+ /Er 3+ ions [ 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , …”
Section: Enhancing Ion Endosomal Escapementioning
confidence: 99%